Existence, Uniqueness and Approximate Controllability of Impulsive Fractional Nonlinear Control System with Nonsingular Kernel - Naji, Fadhil Abbas; Al-sharaa, Iftichar (Iraqi Journal of Science, 2022)
The main aim of this work is to investigate the existence and approximate controllability of mild solutions of impulsive fractional nonlinear control system with a nonsingular kernel in infinite dimensional space. Firstly, we set sufficient conditions to demonstrate the existence and uniqueness of the mild solution of the control system using the Banach fixed point theorem. Further, we prove the approximate controllability of the control system using the sequence method.